Optimizing Village Financial Management: A Study of the Implementation of SAK ETAP at BUMDesa Santong Jaya, Santong Village, Kayangan District, North Lombok Regency - Mahfuz, Muhammad; Harianto, Tedi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the implementation of Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) in the financial management of the Santong Jaya Village-Owned Enterprise (BUMDesa Santong Jaya) in Santong Village, Kayangan District, North Lombok Regency. The research method used is a descriptive qualitative case study approach. Data were collected through in-depth interviews with the BUMDesa director, treasurer, business unit managers, and village government, as well as observation and documentation of financial reports. The study's results indicate that SAK ETAP implementation in BUMDesa Santong Jaya is still not optimal. The financial reports presented are not complete according to SAK ETAP standards, which require a balance sheet, income statement, statement of changes in equity, cash flow statement, and notes to the financial statements. The main obstacles include limited human resource competency in the field of accounting, a recording system that is not fully digital, and minimal ongoing training. This study recommends increasing the capacity of BUMDesa's human resources through SAK ETAP-based accounting training, development of a digital financial recording system, preparation of standardized financial SOPs, and ongoing mentoring from the local government or academics. Optimal implementation of SAK ETAP will increase transparency, accountability, and the quality of BUMDesa's financial information as a basis for strategic decisionmaking